Program Bulan Bakti Gotong Royong Masyarakat (BBGRM) Dalam Meningkatkan Kesejahteraan Sosial - Puspitasari, Kartika Indah; Kuswana, Dadang; Herdiana, Dedi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2025)
One of the values that has long been embedded in the Indonesian nation is mutual cooperation. However, in modern times the spirit of mutual cooperation values has collapsed as a result of social change. The incoming foreign culture has had an impact on society so that now they are very individual, decreasing the sense of togetherness and mutual cooperation. This the spirit of community cooperation needs to be revived through the utilization of mutual cooperation values for welfare. This study aims to determine the program, implementation, and results of the BBGRM program in improving social welfare in Cipadung Kidul Village. This research is a qualitative research using descriptive method. The results of the study show that the activities of the BBGRM program include poskamling, bazaars, MSME coaching, general recitation, counseling, and cleaning the environment. Implementation of activities has 5 stages, namely organizing the implementation team held by LPM, musrengbangkel, implementing activities, fostering control of activity implementation, and monitoring evaluation. The results of the BBGRM program are increasing social welfare conditions and the community happiness index.